The diagnostic value of bronchodilator response in differentiating asthma, COPD, and ACO in fixed airflow obstruction: a retrospective study - Müge Erbay; Olcay Ayçiçek; Aleyna Bektaş Hocek; Kübra Nur Özdemir (BMC Pulmonary Medicine)
Abstract Background An accurate distinction between asthma, chronic obstructive pulmonary disease (COPD), and asthma-COPD overlap (ACO) in patients with fixed airflow obstruction (FAO) is crucial for optimizing treatment strategies and improving clinical outcomes. The role of bronchodilator response in differentiating between these diseases is unclear. We aimed to identify factors that could aid in differential diagnosis. Methods This study employed a single-center, retrospective cohort design at a tertiary referral hospital. Patients with fixed airway obstruction, characterized by a post-bronchodilator FEV1/FVC ratio < 0.7 or below the lower limit of normal spirometry, were included. Receiver operating curve analysis (ROC) was used to evaluate the optimal cutoff values for spirometric data, with the goal of differentiating between ACO patients and those with asthma or COPD. Univariable and multivariable binary logistic regression models were employed to identify the demographic and clinical characteristics associated with ACO. Results Of 301 patients, 41.2% had asthma, 43.9% had COPD, and 15% had ACO. Of the participants 66.4% were male, and the mean age was 61.2 ± 14.3 years. The bronchodilator response (BDR) was significantly higher in the ACO group (280 mL) than in the asthma (190 mL) and COPD (120 mL) groups (p < 0.001). BDR (%) was associated with ACO in both univariate (OR 1.056; 95% CI 1.028–1.084; p < 0.001) and multivariate analyses (OR 1.05; 95% CI 1.01–1.09; p = 0.01). The BDR (ml) had the highest AUC (0.702; p < 0.001), suggesting that it is a moderately predictive diagnostic parameter with a cutoff of ≥ 280 ml (sensitivity: 55.56%; specificity: 77.73%). FEV1 (L) and FEV1/FVC (%) also demonstrated moderate diagnostic values with AUCs of 0.625 and 0.594, respectively. Conclusions This study provides practical cutoff values for BDR, aiding clinicians in distinguishing between overlapping respiratory diseases in a tertiary care settings. An identified BDR cutoff of ≥ 280 mL could serve as a practical tool for distinguishing ACO.